Proper Nouns in Karel Havlíček's Letters - Komárek, Karel (Bohemica Olomucensia, 2016)
There are several hundred proper nouns in the letters written by Czech author Karel Havlíček Borovský (1821-1856), such as nicknames, hypocorisms, Jewish tradesmen's surnames, names of historical places within the Austro-Hungarian Empire, names of streets in Prague, sacred names, or names of institutions and works of art. As far as their language origin is concerned, those are Czech, German, Russian, Polish, and other Slavic names. The article deals with the orthography and morphology of the proper nouns, the then forms of geographical names including exonyms, and puns derived from proper nouns.
Keywords: Karel Havlíček Borovský; proper nouns; personal letters